Women in board: the influence of women as CFO in the level of disclosure of brazilian firms - Segura, Liliane (2015)
This paper centres on the understanding and the relevance of corporate social responsibility (CSR) and their influence on woman as CFO. It will allow to recover the investors’ expectations and to promote corporate business strategies as important issues on the sustainable society. This paper contributes in the domain of CSR and woman literature in two aspects. First, this research provides evidence that corporations include the social dimension in accounting strategies, due to increasing demands of stakeholders. Second, the research presents evidence of trends, pressures and relevance of the level of disclosure to justify that corporations deal with complexity as a consequence of different corporate governance system. The empirical analysis examines the disclosure practices made by all corporations listed on São Paulo Stock Market between the period of December 31, 1991 until December 31, 2014 and several case studies allow the identification of threats, opportunities, strengths and weakness of the CSR and woman literature. This research is centered in Brazil that needs to increase transparency of the annual report, because in the Corruption Perceptions Index (CPI) published by the Transparency International in the year of 2014 occupied the 69th place between 175 countries and in the year of 2014 get the 46th place between 133 countries. This show that CSR practices has moved from theory to reality and there is an evolution perceived by managers. The authors propose that stakeholders’ behaviour must be woman-oriented supported in the firm value conjoin with orientation of social responsibility information. In resume, the debate in which woman have figured certainly call for greater standards of disclosure but right now corporations have been converting into vehicle for social responsibility propaganda instead of the general trend proves that social responsibility web reporting truly affect the firm value.